The Healthy People 2020 Objectives for Kidney Disease: How Far Have We Come, and Where Do We Need to Go? - Wetmore, James B. (Clin J Am Soc Nephrol, 2017)
The Healthy People 2020 initiative established goals for patients with CKD and ESRD. We assessed United States progress toward some of these key goals. Using data from the Centers for Medicare and Medicaid Services ESRD database, we created yearly cohorts of patients on incident and prevalent dialysis from 2000 to 2013. Change in event rate or proportion change over the study years was modeled using Poisson regression with adjustment for age, race, sex, and primary cause of ESRD. For all-cause mortality in prevalent patients, Healthy People 2020 sought approximately 0.8% relative annual improvement; actual improvement was 2.7%. Improvement was greatest for patients ages 18–44 years old (3.8%; P<0.01 versus 2.8% for ages 65–74 years old) and 2.3% even for patients ages ≥75 years old. For mortality in incident patients, the relative annual decrease was 2.1% overall, a twofold improvement over the goal; mortality decreased nearly twice as much in black as in white patients (3.2% versus 1.8%; P<0.001). Geographic variation was substantial; the relative annual decrease was 0.6% in the Midwest and more than fourfold greater (2.7%) in the South. Cardiovascular mortality in prevalent patients decreased dramatically at 5.0% per year, far exceeding the annual goal of approximately 0.8%; the decrease was greatest in patients ages ≥75 years old (5.5%; P<0.001 versus ages 65–74 years old; 5.1%). The relative annual increase in percentages of patients with a fistula at dialysis initiation was 2.4%, roughly three times the goal; the increase was greater for black than white patients (3.2% versus 2.3%; P<0.01). Adjusted regional differences varied greater than twofold: 2.0% for the South versus 4.1% for the Midwest. Thus, although gains have been substantial, not all groups have benefitted equally. Goal development for Healthy People 2030 should consider changes in goal paradigms, such as tailoring by geographic region and incorporating patient-centered goals.